2005
DOI: 10.1152/ajpgi.00072.2005
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine inhibits cytokine-induced apoptosis in human colonic epithelial cells via the pyrimidine pathway

Abstract: tamine inhibits cytokine-induced apoptosis in human colonic epithelial cells via the pyrimidine pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 43 publications
0
35
0
3
Order By: Relevance
“…Since glutamine is able to inhibit TNF-␣ production by interference with the NF-B signaling pathway (14,54), the effect of glutamine on apoptosis could be explained by the observed reduced production of TNF-␣. However, in Caco-2 cells glutamine inhibits death receptor ligandinduced apoptosis by modulating pyrimidine synthesis (15). In the present study we are unable to evaluate which of these proposed mechanisms is crucial for the observed reduced TNF-␣ production and apoptotic response but could reason that by reduction of TNF-␣ and apoptosis in the epithelial layer glutamine is able to reduce disease activity in GvHD.…”
Section: Discussionmentioning
confidence: 60%
“…Since glutamine is able to inhibit TNF-␣ production by interference with the NF-B signaling pathway (14,54), the effect of glutamine on apoptosis could be explained by the observed reduced production of TNF-␣. However, in Caco-2 cells glutamine inhibits death receptor ligandinduced apoptosis by modulating pyrimidine synthesis (15). In the present study we are unable to evaluate which of these proposed mechanisms is crucial for the observed reduced TNF-␣ production and apoptotic response but could reason that by reduction of TNF-␣ and apoptosis in the epithelial layer glutamine is able to reduce disease activity in GvHD.…”
Section: Discussionmentioning
confidence: 60%
“…One study of note by Evans et al indicated that glutamine can prevent intestinal cell apoptosis via the pyrimidine pathway [32]. This provides an interesting mechanistic explanation for glutamine's benefi ts.…”
Section: Discussionmentioning
confidence: 99%
“…A number of in-vitro studies [32,33] have examined the role of glutamine in preventing apoptosis following stress or injury. One study of note by Evans et al indicated that glutamine can prevent intestinal cell apoptosis via the pyrimidine pathway [32].…”
Section: Discussionmentioning
confidence: 99%
“…GS inhibition did not reduce cell cycles but selectively affected cell numbers, similar to inhibiting pyrimidine synthesis. GS was previously shown to selectively support pyrimidine and not purine synthesis, and pyrimidine rather than purine synthesis was required to protect cells from inflammation-induced apoptosis (31,32). Inflammation and tissue injury are physiological conditions of Gln reduction, and GS is de-repressed under low Gln, nucleotide starvation, and by glucocorticoid hormones (22,(33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%